Food safety control in the poultry industry - Mead, G. C. (Geoffrey Charles), 1934- (Cambridge : Woodhead, 2005)
The safety of poultry meat and eggs continues to be a major concern for consumers. This text reviews recent research into identifying and controlling hazards at all stages of the supply chain.
Keywords: Dierlijke voedingsmiddelen; Voedselveiligheid